Peran Perempuan Dalam Aktivitas Ekonomi Keluarga Pada Pekerja Perempuan Di Home Industri Kerupuk Kulit De Jangek Simpang Kawat Kec. Jelutung Kota Jambi - Elsya Octaviany. S; Muthmainnah Muthmainnah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to find out why women or housewives work, what are their reasons for making the decision to work outside the home, to find out differences or changes in the income of housewives before and after working outside the home and what are the constraints of working housewives in improving the family economy. This research is a qualitative research, collecting data by means of interviews, observation and documentation. In this study using data analysis techniques such as data reduction, data presentation, inference and verification as well as the final conclusion. Based on the results of the study it can be concluded (1) the reasons behind women working as employees in the de jangek home industry are due to the insistence on the economic needs of the family, to meet the needs of daily life. (2) there is a change in the income of working housewives so that they can help the family's economy in order to meet family needs and other needs. (3) female workers or housewives have problems at work caused by constraints from the women themselves and external constraint.